The information content of KOF indicators on Swiss current account data revisions - Jan-Egbert Sturm; Jan P.A.M. Jacobs (ETH Zurich, KOF Swiss Economic Institute, 2008)
This paper analyses revisions of Swiss current account data, taking into account the actual data revision process and the implied types of revisions. In addition we investigate whether the first release of current account data can be improved upon by the use of survey results as gathered by the KOF Swiss Economic Institute, ETH Zurich. An answer in the affirmative indicates that it is possible to improve first releases and thereby enhance the current assessment of the Swiss economy.
Keywords: C22; C53; C82; 330; current account statistics; real-time analysis; data revisions; Leistungsbilanz; Außenhandelsstatistik; Statistische Methode; Konjunkturumfrage; Schweiz